2010
DOI: 10.1073/pnas.0914658107
|View full text |Cite
|
Sign up to set email alerts
|

Two closely related endocytic proteins that share a common OCRL-binding motif with APPL1

Abstract: Mutations of the inositol 5′ phosphatase oculocerebrorenal syndrome of Lowe (OCRL) give rise to the congenital X-linked disorders oculocerebrorenal syndrome of Lowe and Dent disease, two conditions giving rise to abnormal kidney proximal tubule reabsorption, and additional nervous system and ocular defects in the case of Lowe syndrome. Here, we identify two closely related endocytic proteins, Ses1 and Ses2, which interact with the ASH-RhoGAP-like (ASPM-SPD-2-Hydin homology and Rho-GTPase Activating Domain-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
117
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(136 citation statements)
references
References 46 publications
19
117
0
Order By: Relevance
“…Linking this compartment to late stages of clathrin-coated pits and newly formed clathrin-coated vesicles is OCRL (oculocerebrorenal syndrome of Lowe), an APPL1-and clathrin-binding inositol 5-phosphatase (Choudhury et al, 2005;Erdmann et al, 2007;Mao et al, 2009). A further OCRL-binding protein, Ses1/2 (also known as IPIP27A/B), associates with the OCRL compartment but because of mutually exclusive binding defines an endocytic sub-population downstream of the APPL1 station (Swan et al, 2010;Noakes et al, 2011). These distinct sub-populations are therefore considered to represent stages along a common maturation pathway that links newly formed endocytic vesicles with the PtdIns3P-enriched early endosome (Huotari and Helenius, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Linking this compartment to late stages of clathrin-coated pits and newly formed clathrin-coated vesicles is OCRL (oculocerebrorenal syndrome of Lowe), an APPL1-and clathrin-binding inositol 5-phosphatase (Choudhury et al, 2005;Erdmann et al, 2007;Mao et al, 2009). A further OCRL-binding protein, Ses1/2 (also known as IPIP27A/B), associates with the OCRL compartment but because of mutually exclusive binding defines an endocytic sub-population downstream of the APPL1 station (Swan et al, 2010;Noakes et al, 2011). These distinct sub-populations are therefore considered to represent stages along a common maturation pathway that links newly formed endocytic vesicles with the PtdIns3P-enriched early endosome (Huotari and Helenius, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…30 It has been shown that these proteins recognize the same binding site in Ocrl1. 42 Interestingly, experimental evidence indicates that Ocrl1 first binds APPL1 on Rab5-positive endosomes to then transition to IPIP27/Ses-containing complexes on a different endosomal compartment ( Figure 3A). 42 This Ocrl1-binding relay event suggests a maturation of the Ocrl1-containing endosomal compartment.…”
Section: Vesicle Trafficking and Cilium Assemblymentioning
confidence: 99%
“…[41][42][43] The ASH domain also constitutes a binding site for Rabs, with the highest affinity for Rab8a, [44][45][46] leading to an interaction that is critical for Ocrl1 role in ciliogenesis. 30,31,47 The RhoGAP-like domain does not exhibit GTPase-activating protein (GAP) activity but mediates binding to the Rho GTPases Rac1 and Cdc42.…”
mentioning
confidence: 99%
“…The protein encoded by HMGN4 is thought to reduce the compactness of the chromatin fiber in nucleosomes, thereby enhancing transcription from chromatin templates, 8,9 while FAM109A encodes a protein that localizes to the endosome and plays a role in endocytic trafficking. 10,11 There were four other loci, ARIH1 (ariadne homolog, ubiquitin-conjugating enzyme E2 binding protein, 1) on chromosome 15, EIF1 (eukaryotic translation Initiation factor 1) on chromosome 17, SLC1A5 (solute carrier family 1 [neutral amino acid transporter], member 5) and CA11 (carbonic anhydrase XI) on chromosome 19, were found to be modestly associated with T1D genetically and epigenetically ( Table 2). EIF1 encodes a known protein translation initiation factor, whereas the protein encoded by ARIH1 is thought to maybe also play a role in protein translation.…”
Section: Combined Analysis Of Ewas and Gwas Data Identified Novel Canmentioning
confidence: 99%